Language Teacher Identity in a Non-Native Context: The case of Teachers of English Language in Ghana - Anku, Joyce (LET: Linguistics, Literature and English Teaching Journal, 2024)
The study investigated how English language teachers in Ghana construct their identities as teachers of English as a Second Language (ESL). Semi-structured interviews were conducted with ESL teachers who were selected through purposive sampling. The data was analysed qualitatively by coding, identifying, categorising and interpreting the emerging themes. It was found that the ESL teachers’ identity is defined by three elements: personal attributes, professional attributes, and contextual factors. On the personal level, the identity of the ESL teachers is characterised by passion, diligence, self-efficacy, and sense of inadequacy. Professionally, subject-matter knowledge, pedagogical knowledge and technological knowledge were found. Lastly, key contextual identity defining factors are curriculum and educational policies, classroom conditions and intrinsic motivation from learners’ success stories. The study recommends further investigation into other factors such as gender on non-native ESL teachers identity formation. Key words: Identity, teacher identity, language teacher identity, identity and teachers of English